2019
DOI: 10.1111/mmi.14211
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into 3‐methylmercaptopropionate metabolism and kinetical regulation of demethylation pathway in marine dimethylsulfoniopropionate‐catabolizing bacteria

Abstract: SummaryThe vast majority of oceanic dimethylsulfoniopropionate (DMSP) is thought to be catabolized by bacteria via the DMSP demethylation pathway. This pathway contains four enzymes termed DmdA, DmdB, DmdC and DmdD/AcuH, which together catabolize DMSP to acetylaldehyde and methanethiol as carbon and sulfur sources respectively. While molecular mechanisms for DmdA and DmdD have been proposed, little is known of the catalytic mechanisms of DmdB and DmdC, which are central to this pathway. Here, we undertake phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…These data suggest that AcuH is the major methylthioacryloyl-CoA hydratase responsible for generating MeSH in these environments. The high abundances of dmdB, dmdC, and acuH may be linked to the high plasticity and flexibility of the corresponding enzymes (Reisch et al, 2011a;Bullock et al, 2014;Shao et al, 2019).…”
Section: The Genetic Potential For Dmsp Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that AcuH is the major methylthioacryloyl-CoA hydratase responsible for generating MeSH in these environments. The high abundances of dmdB, dmdC, and acuH may be linked to the high plasticity and flexibility of the corresponding enzymes (Reisch et al, 2011a;Bullock et al, 2014;Shao et al, 2019).…”
Section: The Genetic Potential For Dmsp Catabolismmentioning
confidence: 99%
“…The DMSP demethylation pathway that can result in the generation of MeSH (Reisch et al, 2011a) is initiated by the DmdA enzyme that was identified in Ruegeria pomeroyi (Howard et al, 2006) and is common in many marine alpha-proteobacteria, including SAR11 bacteria (Reisch et al, 2008(Reisch et al, , 2011b. Many diverse bacteria that do not always have the capacity to demethylate DMSP (lacking dmdA in their genomes) contain dmdBCD/acuH, which encode enzymes that degrade the product of DMSP demethylation, methylmercaptopropionate (MMPA), to generate MeSH (Shao et al, 2019). Thus, the presence of dmdBCD is considered an indicator of MMPA degradation rather than of DMSP.…”
Section: Introductionmentioning
confidence: 99%
“…The work presented in this issue by Shao et al () significantly advances our understanding of how MMPA is further catabolized by two enzymes in this pathway: DmdB, an ATP‐dependent CoA ligase, and DmdC, a flavin‐containing CoA dehydrogenase. DmdB shows high similarity to bacterial short‐chain fatty acid CoA ligases – and, remarkably, the two homologous DmdB proteins of Ruegeria pomeroyi DSS‐3 can accept a range of fatty acids as substrates (Bullock et al , ).…”
Section: Structural Determination Of Enzymes Involved In Dmsp Catabolmentioning
confidence: 99%
“…DmdB shows high similarity to bacterial short‐chain fatty acid CoA ligases – and, remarkably, the two homologous DmdB proteins of Ruegeria pomeroyi DSS‐3 can accept a range of fatty acids as substrates (Bullock et al , ). The crystal structure of DmdB was obtained in the presence of ADP, a competitive inhibitor of this enzyme, and the structure of an inactive Lys523Ala mutant was obtained in complex with AMP and MMPA (Shao et al , ). DmdB forms an asymmetric dimer with ADP bound to one chain while leaving the binding pocket of the other chain empty.…”
Section: Structural Determination Of Enzymes Involved In Dmsp Catabolmentioning
confidence: 99%
See 1 more Smart Citation